Vortioxetine for the Treatment of Depression in Patients with Parkinson’s Disease: A 16-week Pilot, Prospective, Open-label Safety Study - Stocchi, Fabrizio; Bravi, Daniele; Radicati, Fabiana Giada; Coletti, Chiara; Vacca, Laura (Current Neuropharmacology, 2026)
BackgroundParkinson’s disease (PD) is often associated with depression, which poses an additional burden for patients and their families. However, evidence regarding the optimal treatment for depression in PD remains limited, with insufficient data supporting the efficacy of most antidepressant drugs.MethodsThe primary objective of this pilot, prospective, open-label, single-arm study was to analyze the safety and tolerability of vortioxetine drops on depressive symptoms in PD patients over 16 weeks of treatment. The secondary objective was to study vortioxetine's effectiveness on depression.ResultsSixteen out of 20 PD patients who completed the study demonstrated that the treatment was safe and well tolerated; no change in PD symptom severity, abnormality of clinical parameters, body weight, or ECG emerged. The most common side effect was nausea. Depressive symptoms rated by the Beck Depression Inventory and the Hamilton Depression Rating Scale score (HAM-D-17) showed a significant improvement at the end of the study period without a worsening of motor functions, as measured by UPDRS part III. The majority of patients also reported an improvement in depressive symptoms measured by the Patient Global Impression of Improvement scale.ConclusionVortioxetine is a safe and well-tolerated therapeutic approach for depression in Parkinson’s disease. As a secondary objective, an improvement in depressive symptoms was observed. However, the study’s open-label design and small sample size limit the generalizability of the findings.Clinical Trial Registration NumberNCT04301492.
Keywords: open-label